Knowledges and Approaches to Delusional Parasitosis - M. Rezi Rahmanda (HM Publisher, 2022)
Delusional parasitosis, also known as delusional infestation or Ekbom syndrome, is a rare psychotic disease defined by a persistent false belief in the presence of a parasitic infestation of the skin, notwithstanding the absence of medical evidence to support this assertion. There are three types of delusional parasitosis: primary, secondary, and organic. Close relatives might sometimes have the same illusions. This condition, termed as shared psychotic disorder–delusional parasitosis with folie a deux, has been found to occur in 5–15 percent of cases. Patients suffering with delusional parasitosis typically seek medical attention from a variety of specialists. Close interdisciplinary collaboration among doctors is frequently essential for reducing the time required to identify this disease. Initiation of psychopharmacological therapy is difficult because many patients refuse any psychiatric care due to the stigma associated with mental disease and their firm belief that they have a parasite infestation rather than a psychiatric ailment. Many patients experience isolation and the development of depressive symptoms as a result of a lack of understanding, which is why it is critical to win the confidence of such patients when caring for them.